(untitled) (Journal of Informatics and Mathematical Sciences, 2010)
In this research paper we have theoretically analyzed the effects of the angle of convergence and the non-Newtonian characteristics on the performance of an externally pressurized converging circular thrust bearing using Bingham fluid as the lubricant. Since Bingham lubricants are known to have a characterized yield value, there will be a formation of unyielding core in the region between the plates of the bearing. The solutions are obtained for the pressure and load carrying capacity of the bearing for various values of Bingham number and the angle of convergence. The effects of the Non-Newtonian characteristics of the lubricant and the angle of convergence on the performance of the bearing are discussed.